The discourse function of "well", "and" and "now" in turn-initial positions in interruptive speech - Nor, Siti Nurbaya Mohd. (Journal of Modern Languages, 2017)
The central focus of this article is to discuss the discourse functions of "well", "now" and "and" as turn-initial interruptive devices in a radio discourse. To achieve this goal, the study relies on a detailed analysis of transcribed recordings of four radio talk shows. It is observed that the participants' use of these interruptive devices in tum-initial positions in interruptive speech have different pragmatic functions. The present study rests on the conviction that such discourse particles in interruptive speech have certain functions which signal coherence to prior utterance or to earlier segments of the discourse and play interactive roles in the interaction process.